International guidelines for the flow cytometric evaluation of peripheral blood for suspected Sézary syndrome or mycosis fungoides: Assay development/optimization, validation, and ongoing quality monitors. Issue 2 (28th October 2020) - Illingworth, Andrea; Johansson, Ulrika; Huang, Shuguang; Horna, Pedro; Wang, Sa A.; Almeida, Julia; Wolniak, Kristy L.; Psarra, Katherina; Torres, Richard; Craig, Fiona E.
Abstract: Introducing a sensitive and specific peripheral blood flow cytometric assay for Sézary syndrome and mycosis fungoides (SS/MF) requires careful selection of assay design characteristics, and translation into a laboratory developed assay through development/optimization, validation, and continual quality monitoring. As outlined in a previous article in this series, the recommended design characteristics of this assay include at a minimum, evaluation of CD7, CD3, CD4, CD8, CD26, and CD45, analyzed simultaneously, requiring at least a 6 color flow cytometry system, with both quantitative and qualitative components. This article provides guidance from an international group of cytometry specialists in implementing an assay to those design specifications, outlining specific considerations, and best practices. Key points presented in detail are: (a) Pre‐analytic components (reagents, specimen processing, and acquisition) must be optimized to: (i) identify and characterize an abnormal population of T‐cells (qualitative component) and (ii) quantitate the abnormal population (semi/quasi‐quantitative component). (b)Analytic components (instrument set‐up/acquisition/analysis strategy and interpretation) must be optimized for the identification of SS/MF populations, which can vary widely in phenotype. Comparison with expert laboratories is strongly encouraged in order to establish competency. (c) Assay performance must be validated and documented through a validation plan and report, which covers both qualitative and semi/quasi‐quantitative assay components (example template provided). (d) Ongoing assay‐specific quality monitoring should be performed to ensure consistency.